Analysis of indicators of the quality of life of the population in the region (Journal of Economic Research & Business Administration, 2022)
State of the economy any country in the world is characterized, by the level and quality of life ofcitizens. Indicators of the quality life population are important indicators for assessing the specific socioeconomicconsequences ongoing transformations and degree of social tension in society. Improvingquality life population is the most important strategic task of the development society at the presentstage.President K.K. Tokayev noted: «in order to improve the quality of life of every citizen Kazakhstan,the focus will be on infrastructure issues that directly affect the quality life. These are issues in the fieldof housing and communal services, heat and water supply, sewerage, as well as roads, gasification, environmentaland safety problems». Therefore, the quality life of the population becomes relevant in thefocus attention state leadership.The article discusses the methods of determining the quality of life of the population, a review ofthe studies conducted to determine the quality of life. In addition, the article analyzes the indicators forassessing the quality of life of the regions of the Republic of Kazakhstan according to the methodologyproposed by the United Nations, evaluates the socio-economic indicators of the regions and providesrecommendations for its improvement. The scientific novelty of the article was that for each region ofKazakhstan, the estimated HDI index was compared with the Ginny coefficient, the level of quality of life of the population in the regions was determined, shortcomings of the methods were identified. Inaccordance with the results of the study, recommendations were given to improve the quality of life ofthe population.The results of the study will be used as a practical guide for quality of life assessment centers and asa methodological guide for universities.Key words: quality of life, economy, assessment, improvement.